THE INFLUENCE OF CAREER EXPECTATIONS TOWARD WORK READINESS IN SMK STUDENTS - Endah Setyo Wardani (Universitas Sultan Ageng Tirtayasa, 2018)
The research aims to study influence of career expectations toward work readiness in SMK Students. Data collections use questionary, and data analysis uses regression with tool of SPSS version 21.0 for windows, which are colected from 176 students at the XII grade of SMK of Electrical Power Instalation Technique in Malang Raya. the result shows that there is significant influence of career expectations influence toward work readiness by 40,7%.